2008
DOI: 10.4049/jimmunol.181.7.5015
|View full text |Cite
|
Sign up to set email alerts
|

Calcium/Calmodulin-Dependent Protein Kinase (CaMK) IV Mediates Nucleocytoplasmic Shuttling and Release of HMGB1 during Lipopolysaccharide Stimulation of Macrophages

Abstract: The chromatin-binding factor high-mobility group box 1 (HMGB1) functions as a proinflammatory cytokine and late mediator of mortality in murine endotoxemia. Although serine phosphorylation of HMGB1 is necessary for nucleocytoplasmic shuttling before its cellular release, the protein kinases involved have not been identified. To investigate if calcium/calmodulin-dependent protein kinase (CaMK) IV serine phosphorylates and mediates the release of HMGB1 from macrophages (Mφ) stimulated with LPS, RAW 264.7 cells o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
121
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(128 citation statements)
references
References 38 publications
6
121
0
1
Order By: Relevance
“…Recently, it was published that calcium/calmodulin-dependent protein kinase (CaMK) mediated HMGB1 release from macrophages treated with LPS (41). By using various methods to prevent CaMK activation, such as chemical inhibitors (STO609 and KN93), RNA interference, as well as gene knockout mice, the authors showed that CaMK promotes the extracellular release of HMGB1.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was published that calcium/calmodulin-dependent protein kinase (CaMK) mediated HMGB1 release from macrophages treated with LPS (41). By using various methods to prevent CaMK activation, such as chemical inhibitors (STO609 and KN93), RNA interference, as well as gene knockout mice, the authors showed that CaMK promotes the extracellular release of HMGB1.…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46] Recent studies suggest the possible role of elevated cytosolic calcium concentration and calcium/calmodulin-dependent and mitogen-activated protein kinase kinase (MEK)/extracellular signal-regulated kinase (ERK)-dependent regulatory pathways in the nucleocytoplasmic shuttling and release of HMGB1. 39,40 Oh et al showed in monocytes that HMGB1 secretion is induced by a calcium ionophore and inhibited by calcium chelators. 39 These authors found that calcium-dependent protein kinase C phosphorylates HMGB1 in LPS-activated cells.…”
Section: Systemic Inflammation: Three Waves Of Danger Signalingmentioning
confidence: 99%
“…For instance, Youn et al have shown in monocytes that phosphorylation of HMGB1 modulates its nucleocytoplasmic shuttling. [39][40][41] When HMGB1 is phosphorylated, its binding to the nuclear cargo carrier protein, karyopherin-a1, is reduced and HMGB1 is translocated to the cytoplasm and eventually secreted into the extracellular compartment. 42 Translocation of HMGB1 from the nucleus to the cytoplasm also involves its acetylation, 38,39,41 an effect possibly mediated by decreased deacetylase activity.…”
Section: Systemic Inflammation: Three Waves Of Danger Signalingmentioning
confidence: 99%
“…I/R injury is characterized by marked oxidative stress and intracellular calcium overload (38), which activates the release of HMGB1 (32,39). HMGB1 then acts via its receptor (RAGE/TL4) to stimulate the release of proinflammatory cytokines, induce NFκB and enhance myocardial injury (8,9).…”
Section: Discussionmentioning
confidence: 99%